EXTENT OF EARLY CHILDHOOD EDUCATORS AWARENESS OF VIOLENCE AGAINST PERSONS PROHIBITION (VAPP) LAW IN PUBLIC PRIMARY SCHOOLS IN ORUMBA SOUTH LGA OF ANAMBRA STATE - Okoli, Ijeoma A.; Ugwude, Doris I. (Journal of Early Childhood and Primary Education, 2020)
The study was on the extent of early childhood educatorsâ€™ awareness of Violence Against Persons Prohibition (VAPP) law in public primary schools in Orumba South LGA of Anambra State. Three research questions guided the study. The research adopted a descriptive survey research design. The population of the study comprised all the 110 early childhood educators in public primary schools in Orumba South Local Government Area. The entire population was used because it is not too large. The instrument for data collection was a 16 item structured questionnaire developed by the researchers titled â€œEarly Childhood Educatorsâ€™ Awareness of Violence Against Persons Prohibition Law Questionnaire (ECEAVAPPLQ)â€. The Instrument was face validated by three experts. To establish the reliability of the instrument, Cronbach Alpha was used and a reliability coefficient of 0.73, 0.75 and 0.78 was obtained for the three clusters with an overall reliability coefficient of 0.76 obtained for the entire instrument. Data collected were analyzed using the mean score. The findings showed that the extent to which early childhood educators are aware of and implement Violence Against Persons Prohibition (VAPP) law in public primary schools in Orumba South LGA of Anambra State were to a low extent. Findings also revealed that lack of awareness/enlightenment campaign and non-inclusion of teachers in workshops, seminars on VAPP Laws among others were the factors that hinder early childhood educatorsâ€™ awareness of Violence Against Persons Prohibition (VAPP) law in public primary schools. Based on the findings, it was recommended among others that government should organize public enlightenment campaigns to educated the teachers and the public on the existence and scope of the VAPP law and government should organize seminars, workshop for teachers and other stakeholders on the VAPP law.
Keywords: Violence; early childhood educators; prohibition; awareness; law